The anti-politics of health: consensus and conflict in the German natural healing movement, 1890-1910 - Sharma, Avi (Circumscribere International Journal for the History of Science, 2011)
This article argues that “anti-politics” is a useful tool to understand the broad coalitions that mobilized in pursuit of better health and hygiene in Wilhelmine Germany. In an attempt to complement bio-political analysis that focuses on knowledge production and governmentality, and other studies that focus on institutional and party-political conflict, this article shows how members of the German natural healing movement used “anti-politics” to produce consensus across party-political, class and confessional differences. Using two brief-case studies taken from the German natural healing movement, my work suggests that anti-politics created a space where fluid but durable coalitions formed in pursuit of the shared goal of better health and hygiene for the people. In part because these coalitions were regularly dissolved and reformed, historians have spent less time analyzing these spaces of consensus than they have on other aspects of popular health and hygiene movements. This article shows how focusing more attention on the anti-politics of health can illuminate spaces of shared values that transcended party-political, class and confessional differences.